Pemali dan Pola Hidup Sehat Pada Masyarakat Lokal di Kabupaten Gowa - Ahmadin Umar (Jurnal Kajian Sosial dan Budaya: Tebar Science, 2018)
This paper aims to describe the local communities knowledge and belief system of the Pemali tradition in Gowa District, the traditional values ​​of pemali that can construct healthy living behaviors in local communities in Gowa District, the implementation of the value of pemali as a social institution in the modern Gowa community in the modern era. The local people's knowledge and belief system of the Pemali or kasipalli traditions of the local community is formed through socialization in the form of a direct reprimand against a person who is deemed to have violated the matters that are replicated according to their tradition and through the narrative. Traditional Pemali's values ​​that can construct healthy living behaviors in local communities in Gowa District, some of which are the rain shower ban in the first rain after a long drought, the prohibition to roam before dusk, the prohibition of standing in front of the door when opening it in the morning, prohibition of sleep in a haphazard position, and various other types of restrictions.